Effect of Cryopreservation on Sperms Function Parameters and In vitro Fertilization Rate in Mice - Hadi, Ilaf Hassan (The Iraqi Journal of Veterinary Medicine, 2013)
The study was carried out to investigate the effect of cryopreservation in liquid nitrogen (-196ºC) on sperm quality (concentration, motility, morphology) and in vitro fertilization rate (IVF),24 hours post insemination in mice. The sperms were obtained from caudal epididymis of 20 maturemale mice and prepared by Direct Activation Technique after cryopreservation followed by insemination the oocyte of 20 female mice using in vitro fertilization procedure. Results showed that there were significant (P > 0.05) decrease in sperms concentration, motility and morphology postcryopreservation. In addition, the results demonstrated that cryopreservation significantly decreased(P > 0.05) fertilization rate in treated mice (36%) compared to control mice (56%). It is conclusion that frozen sperm can be used without compromising pregnancy chances.